The effects of us covid-19 policy responses on cryptocurrencies, fintech and artificial intelligence stocks: A fractional integration analysis - Emmanuel Joel Aikins Abakah; Guglielmo Maria Caporale; Luis A. Gil-Ala\~na (Cogent Economics & Finance, 2022)
This paper assesses the impact of US policy responses to the Covid-19 pandemic on various technology-related assets such as cryptocurrencies, financial technology, and artificial intelligence stocks using fractional integration techniques. More precisely, it analyzes the behavior of the percentage returns in the case of nine major coins (Bitcoin-BITC, Stella-STEL, Litecoin-LITE, Ethereum-ETHE, XRP (Ripple), Dash, Monero-MONE, NEM, Tether-TETH) and two technology-related stock market indices (the KBW NASDAQ Technology Index-KFTX, and the NASDAQ Artificial Intelligence index-AI) over the period 1 January 2020-5 March 2021. The results suggest that fiscal measures such as debt relief and fiscal policy announcements had positive effects on the series examined during the pandemic, when an increased mortality rate tended instead to drive them down; by contrast, monetary measures and announcements appear to have had very little impact and the Covid-19 containment measures none at all.
Keywords: C22; C32; G15; 330; artificial intelligence; covid-19 pandemic; Covid-19 policies; cryptocurrencies; Fintech; fractional integration